Fixed Points for Multivalued Mappings in Uniformly Convex Metric Spaces - A. Kaewcharoen; B. Panyanak (International Journal of Mathematics and Mathematical Sciences)
The purpose of this paper is to ensure the existence of fixed points for multivalued nonexpansive weakly inward nonself-mappings in uniformly convex metric spaces. This extends a result of Lim (1980) in Banach spaces. All results of Dhompongsa et al. (2005) and Chaoha and Phon-on (2006) are also extended.